MODELS OF SYNTACTIC STRUCTURES IN OLD GERMANIC CONCESSIVE SENTENCES. - TUHAI, Oleksandra (Alfred Nobel University Journal of Philology / Vìsnik Unìversitetu ìm. A. Nobelâ: Serìâ Fìlologìčnì Nauki, 2025)
The proposed article deals with revealing the syntactic profile of the Old Germanic languages, namely, the particularities of the functioning of the syntax and grammatical framework structure of sentences with concessive semantics in the Germanic languages of the ancient period (Old English, Old High German, Old Saxon, Old Norse (Old Icelandic), Gothic, Old Frisian). The study aims to outline the models of syntactic structures of complex sentences with a subordinate / coordinate concessive action in four semantic types of concessive sentences with pure (concessive), conditional, contrastive, and causative semantics of concession across six Old Germanic languages. To meet this objective, a seven-stage methodology was developed based on the use of interdisciplinary tools involving such methods as the method of internal reconstruction, comparative-historical, structural-syntactic, semantic, descriptive methods, analytical and synthetic analysis, and the method of continuous sampling. Based on the internal grammatical reconstruction of Old Germanic concessive sentences of various semantic types, three basic types of their internal framework structure with the governing position of the main V-finite verb in the principal and concessive (or subordinate / coordinate) clauses have been identified as: 1) VXS- / VSX-model with a V-finite verb in the initial position; 2) SVX- / XVS-model with a V-finite verb in the secondary position; 3) SXV- / XSV-model with a V-finite verb in the final position. It has been determined that the syntax of concessive sentences with various semantics of concession in the dynamic synchrony demonstrates the functioning of the identified syntactic models in most semantic types of concessive clauses depending on the specific Old Germanic language. Common and distinctive syntactic particularities of Old Germanic concessive clauses are observed in six configurations as SXV / XSV / VXS / VSX / SVX / XVS with an emphasis on the initial / secondary / final slot positions of the main V-finite verbs in the principal and subordinate (coordinative) clauses. Common syntactic particularities are identified by way of the presence of the same syntactic slot position of the main finite verb – V-initial, V-secondary, V-final as a mutual signal syntactic function or feature in all or certain semantic types of the concessive action in the ancient languages under study. Distinctive syntactic particularities are established by the absence of a certain syntactic slot position of the main finite verb – V-initial, Vsecondary, V-final as a unique signal syntactic feature of the functioning of a certain type of a concessive clause in a certain Old Germanic language. The framework structure of concessive sentences is outlined in terms of the syntactic coherence between pure (concessive), conditional, contrastive, and causative concessive clauses and their corresponding main clauses within the concessive sentences as: “contact – distant” arrangement of the internal framework slot positions of the clausal conjunction with “contact – distant” arrangement of the external framework clause allocation within the whole concessive sentence. The syntactic coherence of concessive / non-concessive conjunctions within clauses of concessive sentences is established as: “contact – distant” arrangement of internal framework conjunction concordance slot positions with “contact – distant” arrangement of internal framework conjunction position within the frame. It was found that the contact clausal conjunction slot positions were common across all Old Germanic languages in four semantic types of sentences with pure (concessive), conditional, contrastive, and causative concession. The distant clausal conjunction slot positions prevailed in Old High German sentences of pure (concessive), contrastive concession; in Gothic sentences of conditional, contrastive, and causative concession. The contact conjunction concordance slot positions are witnessed only in Gothic conditional and Old Frisian causative concessive clauses. The distant conjunction concordance slot positions were common in Old High German conditional, causative concessive clauses, Gothic contrastive concessive clauses, Old Frisian contrastive, causative concessive clauses, and Old English causative concessive clauses.